3D electrochemical model for a Single Secondary Particle and its application for operando analysis. (August 2019) - Song, Jihun; Park, Joonam; Appiah, Williams A.; Kim, Sung-Soo; Munakata, Hirokazu; Kanamura, Kiyoshi; Ryou, Myung-Hyun; Lee, Yong Min
Abstract: We developed a 3D electrochemical model for simulating the electrochemical properties and revealing the internal properties of a single LiFePO4 secondary particle during cycling. The main model parameters, such as the diffusion coefficient and rate constant, were optimized using rate capability data, which have been measured experimentally with a unique single particle measurement technique. We simulated voltage profiles at different c-rates from 2 to 20C, which were approximately equivalent to the experimental voltage profiles. The model estimated real-time overpotential, lithium ion concentration, and state-of-charge within the single particle, which have not been obtained experimentally, while changing design parameters and operating conditions. We validated the reliability and applicability of the model by comparing and analyzing the electrochemical results of various LiFePO4 secondary particles with variable design parameters (i.e., solid volume fraction, secondary particle size, and primary particle size). Graphical abstract: This graphics illustrates a 24 μm LiFePO4 secondary particle consisting of millions of primary particles of 100–200 nm in diameter. We propose a 3D electrochemical model for simulating the electrochemical properties and unveiling the internal properties of the single particle while changing both particle design parameters and operating conditions.Image 1 Highlights: A single LiFePO4 secondary particle shows high capacity retention at high C-rate. The particle was modeled with reflecting the experimental conditions. Performance can be easily predicted by different design parameters using simulation tool. Internal properties of a single particle were observed, which cannot be measured by experimental methods.